The Use of Board Games in Teaching Biodiversity for Sustainable Development: A Quasi-Experimental Method - Satrio Wijoyo; Eeng Ahman; Susanti Kurniawati; Endang Supardi; Mutiah Mutiara Firdaus (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This research aimed to develop and evaluate learning media for sustainable development, specifically through a board game entitled “Board Game Maju Indonesiaku”. The game is designed around the dilemma between biodiversity conservation and economic development, covering four core systems concepts: economics, policy, society, and ecology. The study involved 61 middle school students who played the game for 360 minutes (180 minutes per week). Data was collected through post-test assessments and game performance. An independent t-test was used to analyze the post-test scores. The results showed a significant improvement in students' understanding, with a moderate effect size overall. Notably, there were large effects on the biodiversity concept dimension and moderate effects on the biological conservation concept dimension. The game performance analysis indicated that secondary school students faced challenges in achieving the four sustainable economic development goals. This research highlights the potential of game-based learning as an effective strategy for teaching complex concepts related to sustainable development. It also underscores the need for further refinement of educational tools better to support student understanding and application of these concepts.